Safety of Biologics for Psoriatic Patients with Latent Tuberculosis - Yuan L; Li Y; Lin J; Lin X; Yang B; Man MQ; Wang X (Dove Medical Press, 2023)
Liyan Yuan,* Yang Li,* Junjie Lin, Xiuqiu Lin, Bin Yang, Mao-Qiang Man, Xiaohua Wang Dermatology Hospital, Southern Medical University, Guangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaohua Wang, Dermatology Hospital, Southern Medical University, No. 2 Lujing Road, Guangzhou, 510095, People's Republic of China, Tel +86-20-87255286, Email Wxh_21773@163.com